Maresin 1 Mitigates Inflammatory Response and Protects Mice from Sepsis. (30th November 2016) - Li, Ruidong; Wang, Yaxin; Ma, Zhijun; Ma, Muyuan; Wang, Di; Xie, Gengchen; Yin, Yuping; Zhang, Peng; Tao, Kaixiong
Abstract : Sepsis, frequently caused by infection of bacteria, is considered as an uncontrollable systematic inflammation response syndrome (SIRS). Maresin 1 (Mar1) is a new proresolving mediator with potent anti-inflammatory effect in several animal models. However, its effect in sepsis is still not investigated. To address this question, we developed sepsis model in BALB/c mice by cecal ligation and puncture (CLP) with or without Mar1 treatment. Our data showed that Mar1 markedly improved survival rate and decreased the levels of proinflammatory cytokines in CLP mice such as interleukin-6 (IL-6), tumor necrosis factor- α (TNF- α ), and interleukin-1 β (IL-1 β ). Furthermore, Mar1 reduced serum level of lipopolysaccharide (LPS) and enhanced the bacteria clearance in mice sepsis model. Moreover, Mar1 attenuated lung injury and decreased level of alanine transaminase (ALT), aspartate transaminase (AST), creatinine (Cre), and blood urea nitrogen (BUN) in serum in mice after CLP surgery. Treatment with Mar1 inhibited activation of nuclear factor kappa B (NF-κ b) pathway. In conclusion, Mar1 exhibited protective effect in sepsis by reducing LPS, bacteria burden in serum, inhibiting inflammation response, and improving vital organ function. The possible mechanism is partly involved in inhibition of NF-κ b activation.